Screening for Alcohol Misuse: Practices Among U.S. Primary Care Providers, DocStyles 2016 - Tan, Cheryl H. (Am J Prev Med, 2017)
INTRODUCTION: Excessive alcohol use is associated with car crashes, violence, and multiple disease conditions, including fetal alcohol spectrum disorders. The U.S. Preventive Services Task Force (USPSTF) recommends that primary care providers screen all adults and conduct brief counseling interventions with those who misuse alcohol. The USPSTF prefers use of three screening tools that measure alcohol consumption (Alcohol Use Disorders Identification Test, Alcohol Use Disorders Identification Test-Consumption, and National Institute on Alcohol Abuse and Alcoholism Single Question) because these tools detect the full spectrum of alcohol misuse in adults. This study estimated the prevalence of primary care provider screening practices for alcohol misuse and examined factors associated with using a USPSTF-preferred screening tool. METHODS: In 2016, a cross-sectional analysis was conducted on self-reported 2016 DocStyles data to estimate the prevalence of different screening tools used by 1,506 primary care providers—family practitioners, internists, obstetrician/gynecologists, and nurse practitioners. Adjusted prevalence ratios were calculated using logistic regression to examine the association between provider attributes and use of USPSTF-preferred screening tools. RESULTS: In this study, 96% of providers reported screening patients for alcohol misuse. Among those that screened, 38% used a USPSTF-preferred screening tool. Provider specialty, awareness of USPSTF guidelines, and mode of administering screening tool were associated with using a preferred screening tool. CONCLUSIONS: Although most primary care providers reported screening for alcohol misuse, about two thirds did not use a tool capable of detecting the full spectrum of alcohol misuse. Using suitable screening tools will better identify patients who misuse alcohol and increase the opportunity for appropriate intervention, ultimately helping to reduce the burden from the many conditions associated with excessive alcohol consumption.